2018
DOI: 10.15252/msb.20178129
|View full text |Cite
|
Sign up to set email alerts
|

Proteome‐wide analysis of phospho‐regulated PDZ domain interactions

Abstract: A key function of reversible protein phosphorylation is to regulate protein–protein interactions, many of which involve short linear motifs (3–12 amino acids). Motif‐based interactions are difficult to capture because of their often low‐to‐moderate affinities. Here, we describe phosphomimetic proteomic peptide‐phage display, a powerful method for simultaneously finding motif‐based interaction and pinpointing phosphorylation switches. We computationally designed an oligonucleotide library encoding human C‐termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 83 publications
1
64
3
1
Order By: Relevance
“…We now show that human Scribble binds the APC PBM with low micromolar affinities, with SCRIB PDZ1 domain being the highest affinity site with a K D of 6.0 μ m , whereas SCRIB PDZ3 binds with 18.3 μ m and the SCRIB PDZ2 an affinity of 36.0 μ m . These findings are in disagreement with previous data indicating that APC interacts with SCRIB PDZ1 and 4 domains or with SCRIB PDZ1 and 2 domain only . Instead, the pattern in interactions and affinities we observed for Scribble APC interactions resembles the binding pattern for SCRIB:β‐PIX , which also binds SCRIB PDZ domains 1,2 and 3, with PDZ1 being the highest affinity interactor and PDZ2 the weakest binder.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We now show that human Scribble binds the APC PBM with low micromolar affinities, with SCRIB PDZ1 domain being the highest affinity site with a K D of 6.0 μ m , whereas SCRIB PDZ3 binds with 18.3 μ m and the SCRIB PDZ2 an affinity of 36.0 μ m . These findings are in disagreement with previous data indicating that APC interacts with SCRIB PDZ1 and 4 domains or with SCRIB PDZ1 and 2 domain only . Instead, the pattern in interactions and affinities we observed for Scribble APC interactions resembles the binding pattern for SCRIB:β‐PIX , which also binds SCRIB PDZ domains 1,2 and 3, with PDZ1 being the highest affinity interactor and PDZ2 the weakest binder.…”
Section: Discussioncontrasting
confidence: 99%
“…Importantly, knockdown of human Scribble by RNAi in Caco‐2 cells disrupted the proper localisation of APC at adherens junction . Intriguingly, APC was shown to engage Scribble through its C‐terminal PDZ binding motif binding specifically to the Scribble PDZ1 and 4 domains , however a recent report using peptide‐phage display proteomics approach indicates that the APC C‐terminal PDZ binding motif binds directly to Scribble PDZ1 and 2 .…”
mentioning
confidence: 98%
“…c) In ZO-1 PDZ2, the domain folds from two nonfunctional monomeric domains where βB and βC of the two domains swap in order to complete the fold into the functional dimeric PDZ tandem. [44,45] In addition to the carboxylate-dependent binding of PDZ domains, it has more recently been demonstrated that PDZ domains can also bind internal peptide motifs [42,[46][47][48][49] and phospholipids. e) PDZ domain ligands can also bind using internal motifs where it usually still relies on the insertion of a hydrophobic residue into the binding pocket and either hydrophobic or hydrogen bond interaction coordination of the P −2 , but the interaction also relies on the P +1 or P +2 residue being negatively charged (Glu/Asp), using the carboxylic acid as substitute for the C-terminal.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, proteomic analysis of binding interactions to either a phosphorylated or unphosphorylated version of the C-terminal peptide of ribosomal S6 kinase 1 (RSK1), which can be phosphorylated in response to epidermal growth factor (EGFR) signaling, revealed both enhanced and weakened affinity in the interactome of RSK1:PDZ domain interactions (Gógl et al, 2019). In addition, phage display analysis of the Scribble and DLG1 PDZ domains with unphosphorylated or phosphomimetic peptides of endogenous PDZ ligand sequences again suggest that phosphorylation is a powerful regulatory mechanism for altering PDZ binding and affinity of cellular targets (Sundell et al, 2018).…”
Section: Regulation Of Pdz Domains and Their Targetsmentioning
confidence: 99%